2009
DOI: 10.1126/science.1176077
|View full text |Cite
|
Sign up to set email alerts
|

Eos Mediates Foxp3-Dependent Gene Silencing in CD4 + Regulatory T Cells

Abstract: Regulatory T cells (Treg) are critical to the maintenance of immunological self-tolerance and immune homeostasis by suppressing aberrant or excessive immune responses. Treg specifically express the transcription factor Foxp3, which mediates the coordinate activation of genes such as CTLA-4 and GITR along with repression of T effector cytokines such as interleukin-2 and interferon-γ. Despite progress in understanding mechanisms of Foxp3-dependent gene activation, the molecular mechanism of Foxp3-dependent gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
303
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(317 citation statements)
references
References 32 publications
11
303
1
2
Order By: Relevance
“…Recently, Pardoll and colleagues (Pan et al, 2009) demonstrated that FOXP3-dependent gene silencing involved in downregulation of IL-2 and IFNg in mouse Treg is related to FOXP3 interaction with Eos, a zincfinger transcription factor of the Ikaros family. Direct interaction of Eos and FOXP3 induces epigenetic chromatin modifications that result in gene silencing in Treg.…”
Section: Foxp3 Controls Gene Expression In Tregmentioning
confidence: 99%
“…Recently, Pardoll and colleagues (Pan et al, 2009) demonstrated that FOXP3-dependent gene silencing involved in downregulation of IL-2 and IFNg in mouse Treg is related to FOXP3 interaction with Eos, a zincfinger transcription factor of the Ikaros family. Direct interaction of Eos and FOXP3 induces epigenetic chromatin modifications that result in gene silencing in Treg.…”
Section: Foxp3 Controls Gene Expression In Tregmentioning
confidence: 99%
“…The mechanism by which Eos is involved in Foxp3-dependent gene silencing may be through its corepressors such as C-terminal binding protein 1, which affects histone modification and promoter methylation involved in selective gene silencing. 168 Finally, FOXP3 has also been found to directly interact with c-Rel through its N-terminal region to repress the NF-kB pathway in mature Treg cells. 169 It is highly likely that FOXP3 has many other binding partners.…”
Section: Dynamic Regulation Of the Foxp3 Complexmentioning
confidence: 99%
“…The knockdown of Eos reverses Foxp3-mediated suppression of IL-2 expression, but has little effect on CD25, CTLA-4 and GITR expression. 168 Therefore, Eos is necessary for gene silencing but not for the expression of Foxp3-activated genes. The mechanism by which Eos is involved in Foxp3-dependent gene silencing may be through its corepressors such as C-terminal binding protein 1, which affects histone modification and promoter methylation involved in selective gene silencing.…”
Section: Dynamic Regulation Of the Foxp3 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…It also revealed a number of other transcriptional regulators of the Treg signature, including Eos, Helios, Lef1 and GATA-1, some were shown previously to be associated with Treg cell function. 5,6 The actual contributions of four transcription factors, Eos, GATA-1, Xbp1 and Helios, were then verified by direct expression profiling of Treg cells from the knockout mice of these genes. Surprisingly, the Treg signatures in each of these mutated mice were not altered significantly compared to wild-type cells.…”
Section: 2mentioning
confidence: 99%